Anticipating the Existentialist Hero in Mikhail Lermontov’s A Hero of Our Time and Joseph Conrad’s Nostromo - Nil Korkut Nayki (Gaziantep University Journal of Social Sciences, 2017)
Tracing the similarities and differences between fictional characters belonging to different literary periods may provide good insight into how a character type may evolve through time in line with changing conditions and perspectives. This paper engages in such an activity and attempts to explore the traces of the existentialist and absurdist hero as set out by figures like Jean-Paul Sartre and Albert Camus in two earlier examples of Western literature. The paper first looks at Mikhail Lermontov’s A Hero of Our Time (1840), analyzing the major character, Pechorin as a “superfluous man” – a distinctive character type widely encountered in nineteenth-century Russian literature. It then focuses on Joseph Conrad’s Nostromo (1903) and looks into how the two major characters, Nostromo and Decoud, include traces of the superfluous man on the one hand and look ahead to the existentialist hero on the other. In doing all this the paper suggests that the superfluous man has evolved in time into the existentialist and absurdist hero and that the characters in Lermontov’s A Hero of Our Time and Conrad’s Nostromo clearly anticipate this development.